Motivasi dan Modal Sosial Petani Dalam Pengambilan Keputusan Pinjaman Kredit Pertanian - Wakhidi Wakhidi; Marthen A.I Nahumury; Maria M.D Widiastuti (Universitas Musamus, Merauke, Papua, 2019)
The purpose of this study was to analyze the influence of motivation and social capital on agriculturalcredit decision making. The sample used is the Proportional Random Sampling method, data analysisusing binary logistic regression. The results showed that motivation (X1) and social capital (X2) witha significant level of 95%, influenced the decision of agricultural credit loans with significant valuesof 0.027 and 0.004. Motivated farmers, 3155 times higher in decisions about getting agriculturalcredit loans from other farmers. Farmers who have social capital are 4,231 times higher in decisionsabout getting agricultural credit loans from other farmers. Based on the results, financial institutionsthat facilitate agricultural credit loans can provide the best service by disseminating agricultural loansdirectly to individual or farmer groups.